Rancang Bangun Sistem Informasi Pelacak Status Kemajuan Pemasangan Jaringan PT. Linknet - Narti Narti; Aida Fitri Siregar (LPPM Universitas Bina Sarana Informatika Kampus Kabupaten Banyumas, 2025)
PT. Linknet, Tbk or better known as PT. First Media, Tbk is a company operating in the Internet & Cable TV sector which is headquartered in Jakarta. PT. Linknet has fast, cheap and unlimited internet package services as well as the best HD quality subscription Cable TV options in Indonesia. PT. Linknet, Tbk offers internet services based on hybrid fiber - coaxial or fiber to home which currently has reached 3.12 million homes and has a number of customers/subscribers of approximately 757,000 customers. However, unfortunately, there are many customer complaints regarding the progress status service for installing their internet network, which results in customer dissatisfaction with the company's services. The aim of this research is to overcome existing problems, PT. Linknet, Tbk needs to implement a monitoring/tracking information system for the progress of internet network installation at PT. Linknet, Tbk. The benefit of this research is to make it easier for customers to get information about the progress of installing their internet network to increase customer satisfaction with internet network installation services at PT. Linknet, Tbk. The results of this research are in the form of a website design to track the progress status of internet network installation at PT. Linknet, Tbk whose current status has been tested at PT. Linknet, Tbk.